Whispers of the dead - Kope, Spencer (Kope, Spencer. Special Tracking Unit series, 2018)
"A series of bizarre murders--the victims nearly unidentifiable--forces FBI tracker "Steps" Craig to match wits with the most cold-blooded killer he's ever encountered. A pair of severed feet, stored in a portable cooler, is found in the house of a Federal judge in El Paso. The victim is unknown. The reason the killer went to such trouble--breaking into the judge's house--and what message he intends to send are both mysteries. Magnus "Steps" Craig is part of the elite three-man Special Tracking Unit of the FBI. Called in on special cases where his skills are especially indispensable, Steps is renowned for his incredible ability to find and follow trails over any surface better than anyone else. But there's a secret to his success. Steps has a kind of synesthesia, an ability that allows him to see whatever a person has touched in a unique color--what Steps calls 'shine.' His ability is known to only a few people--his father, the director of the FBI, and his partner, Special Agent Jimmy Donovan. The Special Tracking Unit soon discovers another, earlier victim; again, only the feet were left behind in an icebox. In Spencer Kope's Whispers of the Dead--with few clues besides the body parts left behind--Steps and his team find themselves enmeshed in the most difficult case of their careers. And The Icebox Killer has only just begun"--